Regulation of Synaptic Transmission by RAB-3 and RAB-27 in Caenorhabditis elegans - Mahoney, Timothy R. (The American Society for Cell Biology, 2006)
Rab small GTPases are involved in the transport of vesicles between different membranous organelles. RAB-3 is an exocytic Rab that plays a modulatory role in synaptic transmission. Unexpectedly, mutations in the Caenorhabditis elegans RAB-3 exchange factor homologue, aex-3, cause a more severe synaptic transmission defect as well as a defecation defect not seen in rab-3 mutants. We hypothesized that AEX-3 may regulate a second Rab that regulates these processes with RAB-3. We found that AEX-3 regulates another exocytic Rab, RAB-27. Here, we show that C. elegans RAB-27 is localized to synapse-rich regions pan-neuronally and is also expressed in intestinal cells. We identify aex-6 alleles as containing mutations in rab-27. Interestingly, aex-6 mutants exhibit the same defecation defect as aex-3 mutants. aex-6; rab-3 double mutants have behavioral and pharmacological defects similar to aex-3 mutants. In addition, we demonstrate that RBF-1 (rabphilin) is an effector of RAB-27. Therefore, our work demonstrates that AEX-3 regulates both RAB-3 and RAB-27, that both RAB-3 and RAB-27 regulate synaptic transmission, and that RAB-27 potentially acts through its effector RBF-1 to promote soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) function.